Centro de Estudos Supletivos de Niterói: proposta de reformulação de currículo - Mello, Maria Ines Saemet M. Smiderle (1982)
Since the 1940s when the Serviço de Educação de Adultos was created until the present time, in conjunction with the Centros de Estudos Supletivos, adult education in Brazil has been marked by a continous improvement which keeps within itself a range of ideas in the methodologies used. As a pioneer experience in a substitute course at an elementary school, the Centros de Estudos Supletivos of Niterói was the first to be estabi lished in Rio de Janeiro, and which used a teach-yourself approach. In arder to achieve good results of the work, it was catalogued a bibliography in the area of self-teachingmethods, educational qualification, work force in Brazil, as well as an improvemerit in curriculuns. Next we proceded to a discussion and analisis of the answers based on the questions submitted to the students of the Centros de Estudos Supletivos of Niterói. By this way it was possible to find out the distinguishing characteristics of the school population such as age, the learning stage before they, entered the first- grade school, on one side and, on the other, their aims and aspirations in looking for that kind of course. Having found out the most important pints of the features of the school population, and taking into account the basic references used, it was suggested an af the Centros de Estudos of Niterói. To conduct improvement this activity, it was also suggested, as basic guidelines the search out for an improvement in the students mental ability.